Зв’язок стабільності геному з різними генотипами генів відтворення свиноматок - Драгулян, М.В.; Костенко, С.О.; Сидоренко, О.В. (Фактори експериментальної еволюції організмів, 2013)
Aim. The aim of this study was to investigate the association of genotypes communication complex genes reproductive capacity of sows genome and identify the most promising in terms of increasing bahatoplidnosti studied animal populations combination. Methods. Studies were conducted by using standard molecular genetic and cytogenetic methods. In cytogenetic preparations take into account the level of cells with micronuclei (MN), dual (AH) and apoptotic (AP) cells, and mitotic index (MI). The study of gene polymorphism ESR, NCOA1, PRLR, was performed by PCR–RFLP. FSHR gene polymorphism was performed method Bi-Passa (without restriction). Results. Detected frequencies of alleles and genotypes of genes FSHR, NCOA1, ESR, PRLR and the animals Ukrainian meat and Welsh breeds. Advantage of sows Ukrainian meat and Welsh breeds certain genotypes over their counterparts. A cytogenetic testing sows and found that the frequency of cells with micronuclei affects the twins and the percentage of emergency farrowing. In studying the stability of the genome due to different genotypes of genes reproductive capacity of sows was found that both sows carrier all 4 desired alleles of both species even at high levels of cells with micronuclei is a high percentage of twins and preservation of offspring. Conclusions. Pattern revealed positive effects of alleles ESRB, NCOA1A1, PRLRA, FSHRC. The authentic correlation between productivity performance and the level of micronuclei animals suggests that animals should be selected not only based on DNA markers, but you should still take into account the stability of the genome of pigs. More stable gene was observed in animals with desirable and intermediate genotypes to genes ESR/NCOA1/PRLR/FSHR.

Key words: gene receptor gene, lymphocyte, sow, multiple.